2018
DOI: 10.1371/journal.pone.0203060
|View full text |Cite
|
Sign up to set email alerts
|

Diminishing dry weight is strongly associated with all-cause mortality among long-term maintenance prevalent dialysis patients

Abstract: ObjectivesTo investigate the relationship between dry weight (DW) change and survival in long-term maintenance prevalent dialysis patients.MethodsWe conducted a prospective data collection study with retrospective analysis of the registered data. Patients were followed up for 5 years (1-year observation of DW changes and subsequent 4-year follow-up). The outcome was all-cause mortality. The predictors were 1-year DW change rates. The hazard ratios (HRs) for all-cause mortality were calculated using multivariab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…We showed that in chronic HD patients, risk factors for death differed according to shortterm (≤3 years) or long-term (>3 years) observation. Sato et al [76] showed that the DW obtained from the 1-year observation was a strong predictor of overall death. Kalantar et al [77] investigated weight changes after initiation of dialysis and found that chronic baseline weight loss had a greater impact on mortality than acute weight loss.…”
Section: Weight Change As a Predictor Of Mortalitymentioning
confidence: 99%
“…We showed that in chronic HD patients, risk factors for death differed according to shortterm (≤3 years) or long-term (>3 years) observation. Sato et al [76] showed that the DW obtained from the 1-year observation was a strong predictor of overall death. Kalantar et al [77] investigated weight changes after initiation of dialysis and found that chronic baseline weight loss had a greater impact on mortality than acute weight loss.…”
Section: Weight Change As a Predictor Of Mortalitymentioning
confidence: 99%
“…Few studies have evaluated the association between BW change and mortality among chronic HD patients. 7,[13][14][15] Further, the previous studies have primarily aimed to clarify the impact of obesity on the outcome, as evidenced by the high prevalence of obese patients in those studies. 14,16 Moreover, the slope of BW in these previous studies was generated using a maximum of 6-12 months data, which may not be long enough to exclude the impact of acute disease.…”
Section: Discussionmentioning
confidence: 99%
“…2,22 A limited number of studies captured long-term weight changes as prognosis predictors in maintenance HD patients, and their timeframe of weight change was generally 6-12 months. 7,13,15 Notably, fluctuations in seasonal BW change were reported to be small (around 0.5 kg) in the Japanese dialysis population. 23 Although the association between long-term BW change and mortality in HD patients seems clinically intuitive, the underlying mechanisms of this relationship remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Attainment of actual dry weight can improve patient cardiovascular status and quality of life. 10,11…”
Section: Discussionmentioning
confidence: 99%
“…Attainment of actual dry weight can improve patient cardiovascular status and quality of life. 10,11 Volume overload is not only a major risk factor for cardio-cerebrovascular complications in dialysis patients but is also associated with other adverse effects. For example, chronic volume overload is a risk factor for a microinflammatory state, in which the levels of inflammatory factors or markers, such as CRP, interleukin-6 (IL-6), transforming growth factor-b1, and brain natriuretic peptide, are markedly higher compared with patients that have no volume overload.…”
Section: Discussionmentioning
confidence: 99%